Jezusowe głoszenie Słowa według trzeciego ewangelisty (Łk 4,18n.) - Mielcarek, Krzysztof (Verbum Vitae, 2005)
The article portrays some exegetical and theological features of the text composed by Luke of two short quotations from lsaiah (58,6; 61,1a) Luke shaped it in order to show the figure of Jesus as anointed by the Holy Spirit God's Messenger whose mission is along those of ancient prophets. According to the author of the third gospel the prophecy of ls 61,1f is related to the event of baptism (see Lk 3,21-22), where Jesus was solemnly enthroned in his office ofmessianic messenger. By using the Old Testament promise Luke showed his will of highlighting a prophetic feature of Jesus' life with a strong accent on pneumatology. The character of Jesus' mission is not just spoken words. Jesus' proclamation of salvation works always on two complementary levels: words and deeds (see Ac 10,38). In the same way the third evangelist shows the Gospel spreading out in times o f church activity and in both cases a very important feature of proclamation is an assistanceofthe Holy Spirit (see Lk 4,18f; 5,17; 6,19; 8,46).